Australia Foreign Policy Effect On Indonesia Post Independence of Timor Leste - Zulkarnain; Aos Yuli Firdaus (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2022)
As initially, Australia supported the integration of Timor Leste into the Republic of Indonesia, many events occurred which caused the relationship between Indonesia and Australia to be slightly disturbed. The changes that have taken place in Australia's relationship with Indonesia illustrate the real effects of Timor-Leste's independence. As a result of Australia's role in the East Timorese independence process, its relationship underwent many changes, especially in the political and military fields. The changes taking place in military relations are evident. First, the Agreement on Mutual Security (AMS) was released. Second, the joint training was cancelled, and the troops that used to work together became enemies. Eventually, Australian arms sales to Indonesia were stopped. Changes in the political and diplomatic sphere, including all political visits, were cancelled, and politicians within Australia and Indonesia publicly denounced others. Furthermore, cooperation within the global framework is limited, and the Ambassador's 'high alert' status is. Overall, Australia's relations with Indonesia became hostile. This study aims to determine how the influence of Australian foreign policy on Indonesia after the independence of Timor Leste. This research shows that the independence of Timor Leste and Australia's role in this process directly influenced government relations between Australia and Indonesia. Most Indonesians view the Australian government's actions and policies as separate from its relationship with Australian citizens. However, the relationship between people must still be considered when making policies about Indonesia because of widespread reactions to Australia's role in the East Timorese independence process.